ASPECT OF THE AGREEMENT IN MARRIAGE - wati, Asrat Nita; Tanjung, Dhiauddin (DE'RECHTSSTAAT, 2023)
According to the Civil Code, a marriage agreement is an agreement made by the prospective husband and wife before the marriage takes place, containing the consequences of the marriage on property. There are three forms of the agreement, namely: togetherness of profit and loss, togetherness of results and elimination of togetherness of assets. The marriage agreement must be drawn up by a notary and its contents cannot be changed. While the concept of a marriage agreement in Islamic law states that there are two forms of agreement in a marriage, namely divorce suspension and other agreements that are not contrary to Islamic law, divorce suspension is an agreement pronounced by the groom after the contract is stated in the marriage certificate in the form of a promise of divorce hanging on a certain situation. The marriage agreement in Islamic Law must be ratified by the Marriage Registrar. The results is Marriage agreements that are still taboo in the general public have now become a trend among artists, officials, businessmen, or people with money. They are generally of the view that with the existence of a marriage agreement, the property of each partner is still safe and belongs to them. Even they are not willing if their property is mixed with their partner.